Thyroid hormones and browning of adipose tissue. (15th December 2017) - Weiner, Juliane; Hankir, Mohammed; Heiker, John T.; Fenske, Wiebke; Krause, Kerstin
Abstract: Thyroid hormone (TH) disorders are associated with profound changes in whole body energy metabolism. A major TH target is thermogenic brown adipose tissue (BAT), which can be stimulated directly through thyroid hormone receptors (TRs) expressed in brown adipocytes and indirectly, through TRs expressed in hypothalamic neurons. White adipose tissue (WAT) adopts BAT characteristics by a diverse range of stimuli in a process referred to as browning. It is now understood that TH also induce WAT browning through peripheral and central mechanisms. In this review, we discuss evidence from animal and human studies that TH disorders are associated with changes in both BAT thermogenesis and WAT browning, thereby influencing body temperature and body weight regulation. Highlights: TH play a pivotal role in the regulation of thermogenesis. TH effectuate BAT thermogenesis and BeAT formation by peripheral and central effects in rodents. Activation and recruitment of BAT and BeAT represents a promising therapeutic approach to combat obesity.